A Novel Method to Attain Highly Symmetric Oblique Mandibular Chin-Body Osteotomy. Issue 8 (November 2015) - Fu, Xi; Qiao, Jia; Rui, Lu; Liu, Jian Feng; Gui, Lai
Abstract : Oblique mandibular chin-body osteotomy is a widely used narrowing genioplasty. However, the historic challenge is how to achieve a highly symmetric result of oblique mandibular chin-body osteotomy. Here, we present a novel and simple method to achieve a highly symmetrical mandibular chin-body osteotomy.